Forecasting of International Tourists Arrival in Saarc Region and Prospect of Bangladesh - Mosfiqur Rahman, Md.; Anam, Sayedul; Kumar Chakrabarty, Anuz (International Journal of Engineering and Technology, 2018)
The tourism is the dynamic and earning source of foreign currency in SAARC region. In regarding Bangladesh it is one of the prospective sectors that can contribute to our economy. In this paper, we forecast the international visitorâ€™s arrival in SAARC countries and compare it with Bangladesh.Â In addition, we have discussed the factors that influenced the visitors to visit this territory. The key factors are infrastructure, retail industries, diversification, marketing and media, quality control, affiliation benchmark, and security and safety (Y. Benchabane, 2014).Â Assess the performance of Bangladesh in these key factors and comparing with other countries of SAARC region.Â